The population of bacteria between compost and biochar-compost mixture at the different ratio / Nurul ‘Izzati Mohd. Rahim and Norazlina Abu Sari - Mohd. Rahim, Nurul ‘Izzati; Abu Sari, Norazlina (Faculty of Plantation and Agrotechnology, 2018)
There are a lot of wastes from the agriculture sector especially towards oil palm industry sector. The waste from oil palm such as palm kernel cake (PKC). Palm kernel shell (PKS). Empty fruit bunch (EFB). Mesocarp fibre (MF) and POME. The biochar can be as the one of the soil amendment to the soil. The compost contains much of microbe than biochar. The objectives in this study are to determine which the best ratio of compost of empty fruit bunch (EFB) and biochar of empty fruit bunch (EFB) for microbe population. Second objective is to observe the timing can be effect toward number of microbe population. Use the EFB as the compost, pyrolysis method to make the biochar incubate the biochar and compost together with different ratio and growth on the Nutrient agar (NA) and observed the population of bacteria 24 hours to 48 hours. More time incubate the compost with biochar, more number of bacteria populations because between the compost and biochar at 1:1 rate higher than 2:1 bacteria population. Conclusion, end this studs' shown that more time and number of population was observed.